Predictive Model for Likelihood of Survival of Sickle-Cell Anaemia (SCA) Among Peadiatric Patients Using Fuzzy Logic - Idowu, Adebayo Peter; Aladekomo, Theophilus Adesola; Williams, Kehinde Oladipo; Balogun, Jeremiah Ademola (Discoveries in Agriculture and Food Sciences, 2015)
A fuzzy logic-based system has been applied to a number of cases in medicine especially in the area of the development of diagnostic systems and has been discovered to produce accurate results. In this paper, a fuzzy logic-based system is presented which is used to simulate a prediction model for determining the likelihood of Sickle Cell Anemia (SCA) in individuals given a 3-tuple record containing the level of fetal haemoglobin, genotype and the degree of Anemia. Knowledge was elicited from an expert at Federal Medical Centre, Owo, Ondo State, Nigeria and was used in developing the rule-base and simulated the prediction model using the MATLAB software. The results of the fuzzification and defuzzification of variables, inference engine definition and model testing was also presented and showed that the fuzzy logic based model will be very useful in the prediction of the likelihood of Sickle Cell Anemia (SCA) among Nigerian patients.